A soil archaeal community responds to a decade of ecological restoration. Issue 1 (5th November 2019) - Yan, DongFeng; Gellie, Nicholas J. C.; Mills, Jacob G.; Connell, Gemma; Bissett, Andrew; Lowe, Andrew J.; Breed, Martin F.
Abstract : Large‐scale restoration efforts are underway globally to mitigate the impact of decades of land degradation by returning functional and biodiverse ecosystems. Revegetation is a heavily relied upon restoration intervention, and one that is expected to result in associated biodiversity returns. However, the outcome of such restoration interventions rarely considers recovery to the soil microbiome, a mega‐diverse and functionally important ecosystem component. Here we examine the archaeal component of the soil microbiome and track community change after a decade of eucalypt woodland restoration in southern Australia. We employed DNA metabarcoding to show that archaeal community composition, richness, and diversity shifted significantly, and towards a restored state 10 years after the restoration intervention. Changes in soil pH and nitrate associated with changes to the archaeal community, potentially relating to the pH responsive properties and close relationship with the nitrogen cycle of some archaea. Our study helps shed light on archaeal community dynamics, as no other study has used DNA metabarcoding to study archaeal responses across a restoration chronosequence. Our results provide great promise for the development of molecular monitoring of the soil microbiome as a future restoration monitoring tool.